2016
DOI: 10.1016/j.clae.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the change in posterior corneal elevation and corneal biomechanical parameters after small incision lenticule extraction and femtosecond laser-assisted LASIK for high myopia correction

Abstract: FS-LASIK demonstrated a greater increase in PCE than SMILE only at 12 months, as well as a greater reduction of CRF than SMILE. There were no significant differences in PCE change over time within either group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 24 publications
11
70
0
Order By: Relevance
“…When comparing the stability during the 2-years observation period for the correction of myopia and myopic astigmatism, SMILE was likely to induce fewer instances of myopic regression than wavefront-guided LASIK, but no significant difference between groups. We suppose that factors related to corneal wound healing, inflammation and biomechanical properties could affect myopic regression after the two procedures (Dong et al 2014;Sinha Roy et al 2014;Wu et al 2014;Wu & Wang 2015;Wang et al 2016;Xia et al 2016). Dong et al (2014) reported that SMILE induces a lower degree of keratocyte apoptosis, proliferation and inflammation compared with LASIK.…”
Section: Discussionmentioning
confidence: 98%
“…When comparing the stability during the 2-years observation period for the correction of myopia and myopic astigmatism, SMILE was likely to induce fewer instances of myopic regression than wavefront-guided LASIK, but no significant difference between groups. We suppose that factors related to corneal wound healing, inflammation and biomechanical properties could affect myopic regression after the two procedures (Dong et al 2014;Sinha Roy et al 2014;Wu et al 2014;Wu & Wang 2015;Wang et al 2016;Xia et al 2016). Dong et al (2014) reported that SMILE induces a lower degree of keratocyte apoptosis, proliferation and inflammation compared with LASIK.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported that SMILE minimizes dry eye, and maintains higher corneal sensitivity [4]. In addition, the postoperative corneal biomechanical strength is theoretically greater in comparison to LASIK and FS-LASIK [57]. Therefore, SMILE is considered to be a good selection mode for refractive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Also, highly myopic eyes had the same difference in the change of CRF but not CH in the study by Wang et al. () (Table ). Two of the studies with all degrees of myopia included also showed this difference (Wu & Wang ; Xia et al.…”
Section: Resultsmentioning
confidence: 56%
“…(), which had a higher level of evidence and examined participants with moderate‐to‐high degree of myopia, did not show the same trends in CH and CRF as the study by Wang et al. (, ) even though eyes with low degrees of myopia were not included.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation